Lived Experiences Of DepEd Junior High School Science Teachers in Basey National High School in Implementing Modular Approach of Teaching - Manaba, Reyven A.; Pacula, Ariel G.; Cabading, Izyne Mae C.; Lancanan, Jessica O.; Centinaje, Rose (International Journal of Applied Educational Research (IJAER), 2024)
This study utilized qualitative design, specifically phenomenological research design. Also, in analyzing the data, the researchers used Colaizzi’s method. The study aims to understand the lived experiences of DepEd junior high school science teachers at Basey National High School in implementing a modular approach to teaching. The study findings generated eleven themes, which are: (1) Changes in the time schedule and quality of education. (2) Exposure to COVID-19 (3) Interaction between teachers and students. (4) Time management. (5) Teachers’ flexibility strategies and techniques. (6) Incomplete self-learning material. (7) Student learning and well-being. (8) On-time retrieval of self-learning material. (9) Apathy of students in answering the SLM leads to an incomplete SLM. (10) Teachers have poor work-life balance. (11) paradigm shift in pedagogy.